1981
DOI: 10.1029/ja086ia07p05500
|View full text |Cite
|
Sign up to set email alerts
|

Polarization characteristics of hydromagnetic waves at low geomagnetic latitudes

Abstract: A field campaign, using three magnetometer stations spaced in latitude around the equatorial magnetic field distance L ∼ 1.9, was conducted in early 1979 to investigate the polarization characteristics of hydromagnetic waves at low geomagnetic latitudes. The magnetic pulsations are observed to have periods in the range ∼20‐25 s and to occur primarily in the local morning hours. Statistically, the polarizations at all three stations were predominantly left handed in the local morning hours and right handed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 31 publications
5
18
1
Order By: Relevance
“…These results are in agreement with those provided by previous investigations at low latitudes (Lanzerotti et al, 1981;Yumoto et al, 1985;Ansari and Fraser, 1986), and are consistent with the polarization pattern expected for waves propagating in the antisunward direction (Southwood, 1974;Chen and Hasegawa, 1974).…”
Section: Summary and Discussionsupporting
confidence: 82%
“…These results are in agreement with those provided by previous investigations at low latitudes (Lanzerotti et al, 1981;Yumoto et al, 1985;Ansari and Fraser, 1986), and are consistent with the polarization pattern expected for waves propagating in the antisunward direction (Southwood, 1974;Chen and Hasegawa, 1974).…”
Section: Summary and Discussionsupporting
confidence: 82%
“…: 7.5°N), during the years 1970-88 have been analysed. The results show that in contrast to a well defined local time dependent sense of rotation of polarisation vector reported for high and middle latitude pulsations (Wilson and Sugiura, 1961;Lanzerotti et al, 1981), the equatorial pulsations exhibit a predominantly clockwise sense of rotation particularly from around 22 his to early afternoon hours (13 to 14 his LT) while the events occurring later in the afternoon exhibit, in addition, a counter clockwise sense as well. The results for this equatorial station are consistent with the observations reported for very low latitude stations (Yumoto, 1986), thus indicating a latitudinal factor in characterising the local time dependence of sense of rotation of polarisation vector.…”
contrasting
confidence: 45%
“…Discussion Wilson and Sugiura (1961) were among the first to report on the polarisation characteristics of SCs and the accompanying oscillations in the period range of a few minutes, corresponding to Pc4-5 pulsations, at middle and high latitude stations in the northern hemisphere. They have shown that the sense of rotation ofpolarisation vector for these pulsations shows a reversal across the 10-22 hr meridian-the sense of rotation which is dominantly counter-clockwise between 2200 and 1000 hrs LT becomes mainly clockwise between 1000 and 2200 hrs LT. Lanzerotti et al (1981) and Yumoto et al (1988) point out that the low latitude (L = 1.3-2.11) Pc3 pulsations show a polarisation reversal near local noon with a dominant forenoon counter-clockwise rotation changing to clockwise sense in the afternoon hours. However, coming down to further low latitudes L = 1.55 and L < 1.11 in the case of the regular Pc3 pulsations class not associated with storm sudden commencements, Yumoto (1986a) showed that the sense of rotation ofpolarisation vector which is predominantly right-handed (clockwise) before noon changes to a predominantly left-handed (counterclockwise) near local noon in the northern hemisphere.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The uniform source assumption has been questioned [e.g., Anderson et al, 1976], and significant variations in the amplitude and polarization of Pc3 pulsations over distances of only a few hundred km have been documented even at low latitudes [Lanzerotti et al, 1981]. However, except at long periods (T > 1000 s) and high latitudes, most solid earth induction studies assume that the spatial structure of natural sources can be safely ignored, provided TFs are averaged over a long enough time.…”
mentioning
confidence: 99%